NIR laser pointer for in vivo photothermal therapy of murine LM3 tumor using intratumoral China ink as a photothermal agent - Blázquez Castro, Alfonso (2018)
The photothermal effect is one of the most promising photonic procedures currently under development to successfully treat several clinical disorders, none the least some kinds of cancer. At present, this field is undergoing a renewed interest due to advances in both photothermal materials and better-suited light sources. However, scientific studies in this area are sometimes hampered by the relative unavailability of state-of-art materials or the complexity of setting up a dedicated optical facility. Here, we present a simple and affordable approach to do research in the photothermal field that relies on a commercial NIR laser pointer and a readily available everyday pigment: China ink. A proof-of-concept study is presented in which mice bearing intradermal LM3 mammary adenocarcinoma tumors were successfully treated in vivo employing China ink and the laser pointer. TUNEL and Ki-67 post-treatment tissue assessment clearly indicates the deleterious action of the photothermal treatment on the tumor. Therefore, the feasibility of this simple approach has been demonstrated, which may inspire other groups to implement simple procedures to further explore the photothermal effect.